THE URBAN CENTRES OF MESOAMERICA IN MODERN HISTORIOGRAPHY (City: History, Culture, Society, 2020)
The article highlights the main trends in modern amerindological urban studies. Based on the analysis of the publications, the author identifies the main scientific problems of the history of pre-Columbian American cities. The article also analyzes the main areas of scientific interest in the regional interaction of Mesoamerican urban centres and cooperation with the agricultural rural periphery in the context of local and regional trade relations, permanent and seasonal migration of population. In addition, the work highlights such a special feature of amerindological urban studies as the study of the symbolism of various urban structures and spaces, especially studies of certain types of buildings, their structure, social or religious functions of palaces, squares, playgrounds, temples, fortresses, the singling out the levels of metaphorical and cosmogonic significance of specific parts of cities in South and Central America. At the same time, the author traces the chronological development and changes in the subject of scientific works devoted to the urban centres of Central Mexico and the Yucatan during the 2000 - the 2020s. Thus, the article demonstrates the topics that were relevant in the publications of the 2000s, and which continued to be in the focus of the scientists in the 2010s. In particular, it deals with the study of structural elements of urban architecture, theirdesign, purpose and functional changes during different periods time, in particular hydraulic structures such as dams, bridges, pools, viaducts. In addition, the paper reviews the main trends in pre-Columbian American urban studies that have emerged or become extremely relevant over the last decade. Among the latter, it is worth noting the study of the reflection of social stratification of the population in the geographical zoning of cities and the existence of separate “closed” areas for specific ethnic or social groups, economic specifications of certain areas of cities, as well as those works on urban space analysis in Mesoamerica, which were caused by the influence of political and demographic processes in the region. The article covers the publications of the main scientific amerindological journals and publications, edited in English and Spanish in both Europe and America.
Keywords: urban studies; historiography; pre-Columbian civilizations; Mesoamerica; cities